Pelatihan Penerapan Sistem Kontrol Pengering Ikan Asin Berbasis Multi Attribute Decision Making (MADM) dan Photovoltaic - Tijaniyah; Niken Ayuningsari; Maulidi Eka Gusti (Insan Kreasi Media, 2023)
Technological developments in the fisheries sector are advanced. Conventional techniques are starting to be replaced digitalization. The fishermen catch fish also uses the help of technology. Karanganyar Paiton village is a village located on the seashore. The fish products are sold to the market and some are used as processed food, such as dried salted fish, crackers, shrimp paste and others. This really helps the community's economy. Processed food from fish is also the people's favorite food because it is cheap and delicious, this is often done by the Fish Processed Group (KOI) Village. Dried salted fish is one of the most popular processed fish foods among the public. How to dry fish still uses conventional methods. The disadvantage of this conventional method is that it cannot control the hot weather around Karanganyar village when the rainy season arrives. Many salted fish are not dry enough, which causes the salted fish to smell, taste bitter and tend to be a little wet. If this happens, the salted fish will not be sold and the taste will not be good. Apart from that, Due to the problems above, The advantage of this tool is that it also uses a microcontroller as a heat temperature control system and the Internet of things as a means of informing fishermen that the fish drying process has been completed, thereby reducing overload time for drying salted fish. If the fish is too dry, the texture of the fish will become hard and taste bitter.